Simulating Branching Geometries in Random Trees - Jinasena, K.D.S.; Sonnadara, D.U.J. (University of Colombo, 2011)
Bifurcation branching geometry, which is one of the fundamental branching geometries, was used to simulate the development of random trees using a recursive algorithm. Probability concepts were introduced into the model to generate and control the growth of sub-branches, to replace the use of a fixed set of plant specific parameters. The structural changes of random trees have been studied with the addition of a stochastic nature to the parameters used in the mode